At the end of military intervention historical, theoretical , and applied approaches to transition, handover and withdrawal - Johnson, Robert; Clack, Timothy (Oxford University Press, 2015)
No modern intervention is intended to endure indefinitely; indeed some fashion of exit is always envisioned from the outset. This commitment to an exit is normally informed by an exit strategy. Whilst strategies of closure have been scrutinised recently, not least in light of charges of defective intentions and planning, the relations between the strategies, operations and tactics of exit have not been contextualised.